Pengaruh Likuiditas(CR), dan Leverage(DER) terhadap Profitabilitas Perusahaan: Studi pada PT Telkom Indonesia Tbk (TLKM) Tahun 2017 - 2024 - Difa Zahra Amalia; Herlinda Marga Rita (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on profitability proxied by Return on Assets (ROA) at PT Telkom Indonesia Tbk for the period 2017–2024. The study uses a quantitative approach with a causal associative research type. The data used are secondary data in the form of PT Telkom Indonesia Tbk's annual financial reports obtained from the company's financial reports and the Indonesia Stock Exchange. The data analysis technique uses multiple linear regression with the help of the IBM SPSS program. The results of the study indicate that partially Current Ratio (CR) does not have a significant effect on Return on Assets (ROA) with a significance value of 0.578 (>0.05). Debt to Equity Ratio (DER) also does not have a significant effect on Return on Assets (ROA) with a significance value of 0.467 (>0.05). Simultaneously, the Current Ratio (CR) and Debt to Equity Ratio (DER) do not significantly influence Return on Assets (ROA), as indicated by the F-test significance value of 0.762 (>0.05). The coefficient of determination (R²) value of 0.019 indicates that the two independent variables are only able to explain 1.9% of the variation in company profitability, while 98.1% is influenced by other factors outside the research model. Thus, the profitability of PT Telkom Indonesia Tbk is more influenced by the company's operational and strategic factors than by the level of liquidity and leverage.